Technically food : inside Silicon Valley's mission to change what we eat - Zimberoff, Larissa (Abrams Press, 2021)
"Ultra-processed and secretly produced foods are cheered by consumers and investors because they are plant-based--often vegan--and help address societal issues. An investigative reporter pokes holes in the mania behind today's changing food landscape and clearly shows the trade-offs of replacing real food with technology-driven approximations."--